Description of Notoglanidium pembetadi new species (Siluriformes: Claroteidae) from the Kouilou-Niari River, Republic of the Congo - Vreven, Emmanuel; Zamba, Armel Ibala; Mamonekene, Victor; Geerinckx, Tom (Zootaxa, 2013)
A new claroteid catfish, Notoglanidium pembetadi, is described from the Kouilou-Niari River basin (Republic of the Congo). This species can be distinguished from all other currently known Notoglanidium species as well as from the very similar Anaspidoglanis boutchangai, to which two specimens have erroneously been attributed in the past, by the following combination of characters: II, 10–13 dorsal-fin rays; long dorsal-fin base (21.1–24.4% SL); short predorsal distance (30.1–33.5% SL); and short prepelvic distance (40.1–45.4% SL).